PENGEMBANGAN MODUL TEMATIK BERBASIS INKUIRI PADA TEMA 2 SELALU BERHEMAT ENERGI SUBTEMA 2 MANFAAT ENERGI KELAS IV SD/MI - Astuti, Nindi Widi; Astuti, Mardiah; Sofyan, Fuaddilah Ali (Jurnal Multidisipliner Bharasumba, 2022)
Education is a very important requirement in improving the quality of human resources. Through education, humans can find new things that can be developed and obtained to face the challenges that exist in accordance with the times. The national education system must always be developed in accordance with the needs and developments that occur at the local, national and global levels. Based on the description of the background above, the author will conduct research with the title "Development of Inquiry-Based Thematic Modules on Theme 2 Always Save Energy Sub-theme 2 Benefits of Energy Class IV SD/MI". The purpose of this research is to test and produce valid, practical and effective module teaching materials. This study uses the type of research development or Research and Development, namely the research method used to produce products with a development model that follows the flow of formative evaluation (Tessmer) design. The limited trial in this study was carried out on 19 grade IV A students at SD Negeri 32 Rantau Bayur. Data collection techniques used in this study were validation tests on several experts and student respondent questionnaires. The results showed that the Validator Recapitulation (1) Design experts 77% with valid categories; (2) 98% Linguists with very valid category; (3) Material experts 83% with very valid category; and Practical Recapitulation (1) One to One 83% with very practical category; (2) Small Group 82% with very practical category; and the recapitulation of the effectiveness of the post-test results obtained a figure of 87% in the very effective category.